2012
DOI: 10.4028/www.scientific.net/amm.161.113
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Immunological Evaluation of Chitosan Nanoparticles as Adjuvants for Bovine Coronavirus N Protein

Abstract: Chitosan nanoparticles (CNP) loaded with nucleocapsid protein of bovine coronavirus (BCV N) were prepared by ionic cross-linking method using sodium tripolyphosphate (TPP) as cross-linking agent. CNP loaded with BCV N protein was intramuscularly administered into Balb/c mice. Serum levels of anti-N protein IgG, IgM, and IgA antibodies were dynamically monitored by indirect ELISA method. Results showed that in the BCV N-loaded chitosan group, both IgA and IgG levels were found to increase significantly after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The IgM content in serum increased after the second immunization in the BCV N protein-loaded CNP group. These findings indicate that CNP can be used as a novel adjuvant in veterinary vaccine field [ 130 ].…”
Section: Antiviral Nanomaterials and Delivery Systems Of Polysaccharimentioning
confidence: 99%
“…The IgM content in serum increased after the second immunization in the BCV N protein-loaded CNP group. These findings indicate that CNP can be used as a novel adjuvant in veterinary vaccine field [ 130 ].…”
Section: Antiviral Nanomaterials and Delivery Systems Of Polysaccharimentioning
confidence: 99%
“…Furthermore, high concentrations of AgNPs immobilized in CNFS could significantly reduce the virus in logs of 10 CFU/ml, while CNFS provided a minor reduction in influenza A viruses. In addition, Sun et al (2012) investigated the use of chitosan nanoparticles loaded with nucleocapsid proteins from bovine coronavinis (BCV N). This process used the ionic crosslinking method with sodium tripolyphosphate as a crosslinking agent.…”
Section: Antiviral Chitin/chitosan Nanofiber Mask Against Covid-19mentioning
confidence: 99%
“…Such a difference could be due to the low dosage of bare or nanoencapsulated DNA. In a study, Sun et al showed that intramuscular administration of chitosan-encapsulated N protein of bovine CoV (BCV N) NPs can significantly enhance IgA and IgG levels as compared to Montanide ISA 206, an oil adjuvant, effectiveness of chitosan NPs to be used as an adjuvant for BCV N protein [147]. Altogether, nanotechnology-based vaccine formulations are promising immune cell activators and antigen carriers for vaccination, but further studies are still required.…”
Section: Convalescent Plasmamentioning
confidence: 99%